Psicologia e pobreza no Brasil: limites e perspectivas da produção de conhecimento e atuação do psicólogo - Dantas, Cândida Maria Bezerra (2007)
Poverty is a main theme in Brazil: according to official data, poverty reachs 70 million Brazilian people, and, between them, 20 million are unable to provide their basic needs. Psychology, as a welfare profession, and given its historical concerns with social actions, could not be away from this theme. Based on this, we ask: Which answers Psychology can provide, toward both the production of knowledge and the practice about social reality? The purpose of this paper is to investigate the psychological scientific production on poverty and the propositions, limits and impacts of psychological actions. We carried out a three stages documental based study analyzing Brazilian psychological literature: (1) online databases survey (312 papers identified); (2) 109 scientific abstracts accessed and coded; (3) selected 47 scientific papers read and analyzed. Results are presented in three sections: general description of the selected scientific production; characterization of the role of poverty in psychological literature; and themes presented at the papers. The academic production about the main theme (poverty) is dispersed, heterogeneous, and related to other fields of knowledge. Poverty is presented at these studies in many ways, such as: a criterium for sample design and the assessment of its psychological impacts; reports on professional experience with poor population; descriptions of this population group; relationship between poverty and others social themes; developmental and learning problems of poor children. In general, it appears that Psychology has improved the scientific production and experiences with poor population. However, it is necessary to build up theories and technical innovations and also to understand structural boundaries for professional practice with this population group